Shakespeare’s: his 450th birth anniversary and his insights into neurology and cognition - Marleide da Mota Gomes (Arquivos de Neuro-Psiquiatria)
The works of William Shakespeare (1564-1616), the greatest dramatist and poet of the English language, reflect several cultural values of the Western world which are also shared by other cultures. On his 450th birthday, many of his concepts are admired as descriptions of human feelings and neurological phenomena, demonstrating his insights into what it is today considered cognitive neuroscience